Upaya Memenuhi Kebutuhan Air Irigasi melalui Pemanfaatan Situ Rancabala di Desa Cimari Kecamatan Cikoneng Kabupaten Ciamis - Martina, Gina (LP2M-PMP Universitas Siliwangi, 2020)
This study has a background that Situ Rancabala is used by farmers in Cimari Village as fulfillment of irrigation water needs. So that water can cover the entire area of rice fields every year. This study examined the description of the physical conditions of Situ Rancabala and the use of Situ Rancabala to meet irrigation water needs. Cimari village has five hamlets namely Jalatrang Hamlet, Wetan Hamlet, Sukasari Hamlet, Kulon Hamlet, and Ranji Hamlet. The activities of the community in Cimari Village, which have a livelihood as farmers, mostly manage rice fields belonging to the village government or kalungguhan. The main problems in this study are: (1) What is the description of Situ Rancabala's physical condition in Cimari Village, Cikoneng District, Ciamis Regency? (2) What is the use of Situ Rancabala for irrigation in Cimari Village, Cikoneng District, Ciamis Regency ?. The method that I use in this study is a descriptive method with a quantitative approach. Data collection techniques used are observation, interviews, literature studies, documentation. The population used was 111 people and a sample of 50 people was taken. The results showed that efforts to meet irrigation water needs through the use of Situ Rancabala in Cimari Village, Cikoneng Subdistrict, Ciamis Regency can be seen from the physical condition of Situ Rancabala starting from the Situ Rancabala area, Situ Rancabala depth, water volume, water rate, water level, and source water. Besides that, it can be seen from the use of Situ Rancabala as a source of irrigation and the water needs needed for rice from seedling planting, paddy processing, fertilization, pest control, irrigation, post-harvest until the marketing of products in Cimari Village, Cikoneng District, Ciamis Regency.